INTEGRASI NILAI-NILAI ISLAM DI SMP TERPADU AL MA'SHUM MARDIYAH - Halfira Rahmah, - (2022)
Education is a conscious and planned effort in the form of a learning process that aims to shape students into human beings who have faith and piety, have noble character, are healthy, knowledgeable, capable, creative, independent and responsible. Through education, the character of students is expected to be formed through teaching from various subjects as well as by inculcating values in them. But in practice, the inculcation of values is not entirely implemented in all subjects. There is a phenomenon of educational dichotomy that separates subjects from grades. This causes students who are confused to accept science and a serious moral shift. This study aims to describe the concept of integrating Islamic values in schools. In particular, the objectives of this study are to: 1) Explain the concept of integration of Islamic values in the learning system at SMP Terpadu Al Ma'shum 2) Explain the implementation of the concept of integration of Islamic values in the learning system at SMP Terpadu Al Ma'shum Mardiyah 3 ) Explaining the problems faced by SMP Terpadu Al Ma'shum Mardiyah in integrating Islamic values into school activities. This research uses a descriptive qualitative approach. This research makes the researcher as the key instrument. Data collection uses documentation study techniques, observations and interviews. The data analysis technique begins with data reduction, data display and drawing conclusions. The result of this research is the concept of integration of Islamic values at SMP Terpadu Al Ma'shum Mardiyah in the form of a learning process that links all general and religious subjects with verses of the Qur'an or Hadith.